A comparison of two methods for Boolean query relevance feedback - Salton, Gerard 1927-1995; Fox, Edward Alan 1950-; Voorhees, Ellen (1983)
The relevance feedback process uses information derived from an initially retrieved set of documents to improve subsequent search formulations and retrieval output. In a Boolean query environment this implies that new query terms must be identified and Boolean operators must be chosen automatically to connect the various query terms. In this study, two recently proposed automatic methods for relevance feedback of Boolean queries are evaluated and conclusions are drawn concerning the use of effective feedback methods in a Boolean query environment.
Keywords: Information retrieval -- Automation; Online bibliographic searching